2019
DOI: 10.1111/anae.14826
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patient attitudes to behaviour change before surgery to reduce peri‐operative risk: preferences for short‐ vs. long‐term behaviour change

Abstract: Pre-operative intervention to improve general health and readiness for surgery is known as prehabilitation. Modification of risk factors such as physical inactivity, smoking, hazardous alcohol consumption and an unhealthy weight can reduce the risk of peri-operative morbidity and improve patient outcomes. Interventions may need to target multiple risk behaviours. The acceptability to patients is unclear. We explored motivation, confidence and priority for changing health behaviours before surgery for short-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Unhealthy behaviours and lifestyle factors frequently cluster in the same individual and may be particularly common in surgical populations, driving development of surgical pathologies. 13,14 In our recent study, 42% of patients demonstrated two or more risk factors. This emphasises both the possibility of a 'risk multiplier' effect from several risk factors, and the need for multimodal intervention to modify factors simultaneously in the potentially time-pressured preoperative window.…”
Section: Fit To Fight: Prehabilitation For Major Surgerymentioning
confidence: 85%
See 3 more Smart Citations
“…Unhealthy behaviours and lifestyle factors frequently cluster in the same individual and may be particularly common in surgical populations, driving development of surgical pathologies. 13,14 In our recent study, 42% of patients demonstrated two or more risk factors. This emphasises both the possibility of a 'risk multiplier' effect from several risk factors, and the need for multimodal intervention to modify factors simultaneously in the potentially time-pressured preoperative window.…”
Section: Fit To Fight: Prehabilitation For Major Surgerymentioning
confidence: 85%
“…Our recent research has highlighted a high degree of patient motivation to change behaviour for perioperative benefits, however a comparative lack of confidence identified a need for structured Prehabilitation support. 13 The wider public health opportunity offered by surgery to embed lasting lifestyle change should not be ignored. Effective prehabilitation is person centred, placing the patient at the core of their perioperative journey.…”
Section: Fit To Fight: Prehabilitation For Major Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has identified that short-term health benefits were more influential for behaviour change than long-term benefits. 26 This provides further support for the dental setting being a teachable moment where short-term benefits can be seen.…”
Section: Sca In Other Settingsmentioning
confidence: 79%